(untitled) (Technical Journal, 2019)
A project manager is the person who has the overall responsibility for the successful initiation, planning, design, execution, monitoring, controlling and closure of a project. Project manager is responsible to complete the project within time, cost and quality towards making the project a success. Construction industry plays an important role in the economy of the country. The industry, however, is beset with many challenges, including delivering projects within cost, time and quality. Therefore project manager is a critical resource in the project to achieve its objectives. Sadly, the role of the project manager is often overlooked. It is assumed that the leadership role of the project manager is measured against time, cost, quality, and customer satisfaction. The importance of this study is to find various roles that project managers ought to play for improving project performance. Good project management practices and competent project managers always deliver better result.